1987
DOI: 10.2464/jilm.37.824
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue crack propagation in Al-Si alloy castings.

Abstract: Permanent mold castings of high purity binary Al-Si alloys (Si: 3, 7, 12 and 20%) were tested. The fatigue crack propagation in as-cast alloys in the Paris regime is seriously influenced by Si concentration less than eutectic composition. Al-20%Si alloy is less stable in fatigue crack propagation than the other alloys. Solution treated high Si alloys show slower rates of fatigue crack propagation than as-cast alloys. The fact depends on strengthening of the matrix, forming of eutectic Si particles into spheres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…Static fracture phenomena of the hard second phase during fatigue crack growth have been reported in metal matrix composites containing a compound phase such as SiC particle-reinforced Al alloy composites, 24,25) WC-Co based cemented carbides [26][27][28] and Al-Si based casting alloys with hard Si particles as the second phase. [29][30][31][32][33] Kobayashi et al 24) investigated the SiC particle behavior during fatigue crack growth in Al alloy composites, and pointed out that fatigue crack growth was promoted by delamination between the SiC particles and the matrix and/or cleavage cracking of the SiC particles themselves, and the crack growth rate was accelerated by an increase in the SiC volume fraction. In addition, Sunouchi et al 28) examined the fatigue crack growth mechanism of WC-Co sintered materials using an acoustic emission technique, and concluded that the crack growth rate was accelerated by brittle fracture of WC particles and the particle fracture frequency increased with an increase of K max .…”
Section: (G))mentioning
confidence: 99%
“…Static fracture phenomena of the hard second phase during fatigue crack growth have been reported in metal matrix composites containing a compound phase such as SiC particle-reinforced Al alloy composites, 24,25) WC-Co based cemented carbides [26][27][28] and Al-Si based casting alloys with hard Si particles as the second phase. [29][30][31][32][33] Kobayashi et al 24) investigated the SiC particle behavior during fatigue crack growth in Al alloy composites, and pointed out that fatigue crack growth was promoted by delamination between the SiC particles and the matrix and/or cleavage cracking of the SiC particles themselves, and the crack growth rate was accelerated by an increase in the SiC volume fraction. In addition, Sunouchi et al 28) examined the fatigue crack growth mechanism of WC-Co sintered materials using an acoustic emission technique, and concluded that the crack growth rate was accelerated by brittle fracture of WC particles and the particle fracture frequency increased with an increase of K max .…”
Section: (G))mentioning
confidence: 99%
“…The critical point of stress intensity factor (DK) in fracture mode defined as fracture toughness (K IC ) of the material which is ranged in 17.6-20.7 MPa ffiffiffiffi m p for AZ31B magnesium alloy. 44,45 The relationship between the virtual crack size and the corrosion time was obtained by curve-fitting, as reported in equation (11).…”
Section: Materials and Testsmentioning
confidence: 99%
“…The virtual crack size is only affected by the corrosion time, and no significant influences could be observed on virtual crack size upon increasing the maximum stress. Thus, in Table 6, the mean values of different corrosion times have also been reported and used to propose equation (11).…”
Section: Fatigue Testsmentioning
confidence: 99%
See 2 more Smart Citations